A note on “Generalized fuzzy linear programming for decision making under uncertainty: Feasibility of fuzzy solutions and solving approach” - Kumar, Amit; Appadoo, S.S.; Bector, C.R. (Information sciences, 2014)
In this short note, we point out that the paper entitled above suffers from certain mistakes.